Structure and mechanism of the mitochondrial calcium transporter NCLX - Minrui Fan; Chen-Wei Tsai; Jinru Zhang; Jianxiu Zhang; Aswini R. Krishnan; Tsung-Yun Liu; Yu-Lun Huang; Deniz Aydin; Siyuan Du; Briana L. Sobecks; Madison X. Rodriguez; Andrew H. Reiter; et al. (Nature, 2025)
Abstract As a key mitochondrial Ca 2+ transporter, NCLX regulates intracellular Ca 2+ signalling and vital mitochondrial processes 1–3 . The importance of NCLX in cardiac and nervous-system physiology is reflected by acute heart failure and neurodegenerative disorders caused by its malfunction 4–9 . Despite substantial advances in the field, the transport mechanisms of NCLX remain unclear. Here we report the cryo-electron microscopy structures of NCLX, revealing its architecture, assembly, major conformational states and a previously undescribed mechanism for alternating access. Functional analyses further reveal an unexpected transport function of NCLX as a H + /Ca 2+ exchanger, rather than as a Na + /Ca 2+ exchanger as widely believed 1 . These findings provide critical insights into mitochondrial Ca 2+ homeostasis and signalling, offering clues for developing therapies to treat diseases related to abnormal mitochondrial Ca 2+ .